2019
DOI: 10.5114/kitp.2019.83941
|View full text |Cite
|
Sign up to set email alerts
|

An overlooked fact: thrombocytopenia following bioprosthetic aortic valve replacement

Abstract: Introduction Thrombocytopenia observed after bioprosthetic aortic valve replacement has remained a puzzle to solve. Aim To analyze thrombocytopenia occurring after bioprosthetic aortic valve replacement by comparison to mechanical aortic valve replacement and coronary artery bypass grafting procedures. Material and methods The study was conducted retrospectively on a total of 297 patients who underwent bioprosthetic aortic valve replacement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Postoperative moderate-severe thrombocytopenia was more common in patients with bioprosthetic aortic valve replacement than in patients with CABG surgery and mechanical aortic valve replacement on the second postoperative day. 20 Similar to this study, we found that the presence of moderate-severe thrombocytopenia in bioprosthetic valves was statistically significantly higher (53.1%, 17/32) compared with patients with mechanical valves (32.6%, 44/135) ( p = 0.030). However, the number of patients with mechanical valves was about four times those with bioprostheses.…”
Section: Discussionsupporting
confidence: 88%
“…Postoperative moderate-severe thrombocytopenia was more common in patients with bioprosthetic aortic valve replacement than in patients with CABG surgery and mechanical aortic valve replacement on the second postoperative day. 20 Similar to this study, we found that the presence of moderate-severe thrombocytopenia in bioprosthetic valves was statistically significantly higher (53.1%, 17/32) compared with patients with mechanical valves (32.6%, 44/135) ( p = 0.030). However, the number of patients with mechanical valves was about four times those with bioprostheses.…”
Section: Discussionsupporting
confidence: 88%
“…Disturbance of thrombopoiesis through cytokines or thrombopoietin, antibodies against megakariocytes, platelet activation resulting in microvascular thrombi, organ sequestration or their phagocytosis, as well as cytotoxicity and apoptosis induced by bacterial products may all be involved [ 48 , 49 ]. Confounding causes include heparin-induced thrombocytopenia or transient postoperative thrombocytopenia related to bioprosthetic valves [ 50 ]. In our case the thrombocytopenia, although improved after anticoagulation, resolved only after surgery, likely related to the removal of pathogen source [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confounding causes include heparin-induced thrombocytopenia or transient postoperative thrombocytopenia related to bioprosthetic valves [ 50 ]. In our case the thrombocytopenia, although improved after anticoagulation, resolved only after surgery, likely related to the removal of pathogen source [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research of the scientific literature revealed limited information regarding cases of patients with heart valve prostheses and associated thrombocytopenia. The few existing reports presented the appearance within the immediate time span after the surgical or interventional procedure (6)(7)(8). Related to the thrombocytopenia causes, studies present numerous and varied conditions that can trigger it.…”
Section: Discussionmentioning
confidence: 99%